Cassation Judge Considerations in Overturning the Surabaya District Court’s Acquittal in a Murder Case - Maman Abdurakhman; Deny Guntara; Muhamad Abas (UNISSULA, 2025)
The responsibility of a judge is not only to the State but also to God Almighty. The panel of judges in deciding a case always carries a message with the sentence “Justice is based on the one and only God.” The Surabaya District Court Judge acquitted the defendant in a murder case because he was not proven to have committed the crime charged by the public prosecutor, namely “Article 338 of the Criminal Code or both Articles 351 paragraph (3) of the Criminal Code or the first three Articles 359 of the Criminal Code and both Articles 351 paragraph (1) of the Criminal Code.” The public prosecutor filed an appeal to the Supreme Court. This study aims to analyze how the public prosecutor will file an appeal in a murder case that was acquitted by the Court and how the cassation judge considered it in decision Number 1446 K / Pid / 2024? This research was conducted normatively by examining library materials and applicable regulations. The stages or process of submitting a cassation by the public prosecutor to the Supreme Court are stated in “Article 244, Article 245, Article 246, Article 247 and Article 248 of the Criminal Procedure Code concerning cassation examination”. The main finding in the description of the judge's considerations, the actions carried out by the Defendant clearly fulfill the elements of a criminal act as stated in the alternative charge of the second combination of Article 351 paragraph (3) of the Criminal Code. Thus, the Defendant was found guilty legally and convincingly, and was sentenced to five years imprisonment.